2012
DOI: 10.1155/2012/697240
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Coronary Heart Disease: A Risk Factor for the Global Epidemic

Abstract: Cardiovascular disease remains a leading cause of death in the United States and the world. In this we will paper focus on type 2 diabetes mellitus as a risk factor for coronary heart disease, review the mechanisms of atherogenesis in diabetics, the impact of hypertension and the treatment goals in diabetics, the guidelines for screening, and review the epidemiologic consequences of diabetes and heart disease on a global scale. The underlying premise to consider diabetes a cardiovascular disease equivalent wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 63 publications
(62 reference statements)
2
65
0
5
Order By: Relevance
“…This includes a higher incidence of cardiovascular diseases and risk of cardiovascular death compared to the background population (Chiha, Njeim, & Chedrawy, 2012). One major cause of morbidity and mortality in persons with diabetes is diabetic nephropathy, which is the leading cause of chronic kidney disease (CKD) and end-stage renal disease worldwide (Pugliese, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This includes a higher incidence of cardiovascular diseases and risk of cardiovascular death compared to the background population (Chiha, Njeim, & Chedrawy, 2012). One major cause of morbidity and mortality in persons with diabetes is diabetic nephropathy, which is the leading cause of chronic kidney disease (CKD) and end-stage renal disease worldwide (Pugliese, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both uncontrolled hypertension and diabetes have strong influence on ACS. [19][20] Another notable fact is that the patients of upper and middle class have a strong tendency to go to specialized centers in Dhaka or Chittagong for better treatment of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and coronary artery disease are often present in the same patient [20]. Prior clinical studies have shown that diabetic patients have a higher mortality rate than nondiabetic patients after myocardial infarction [21,22].…”
Section: Introductionmentioning
confidence: 99%